Immunohistochemical Expression of BCL6 in Nodal and Extranodal Cases of Diffuse Large B Cell Lymphoma-A Study in a Tertiary Care Hospital in Islamabad - Khan, Armaghana Qamar (International Journal of Pathology, 2023)
Background: Diffuse Large B Cell Lymphoma (DLBCL) is a common non Hodgkin lymphoma with a high mortality rate. BCL6 is the common oncogene that is mutated in DLBCL. Special therapeutic agents have been designed to target the mutated BCL6 gene. Therefore, DLBCL is a curable malignancy, and patients who are positive for BCL6 gene expression have better prognosis and survival, as they benefit from targeted therapy against BCL6 mutations.Objectives: To determine BCL6 expression in DLBCL in nodal and extranodal cases.Material & Methods: This descriptive cross-sectional study was carried out in the Pathology department of Pakistan Institute of Medical Sciences Islamabad. Duration of study was 3 years and 2 months, from 1st October 2014 to December 2017. Lymph node biopsies and surgical specimens with clinical suspicion of a mass were processed through various steps; slides were prepared and stained with H&E. A comprehensive panel of antibodies including LCA, Pan B (CD-20), Pan T (CD-3), Ki-1 (CD- 30), (CD 15), (CD 10), (BCL 2), and MIB-1 (Ki-67) was applied on cases with morphology of lymphoproliferative disease. LCA, CD20 positive cases, and those cases with Ki 67 of more than 40% were selected for BCL6 protein expression Immuno-staining with BCL6 was done after numerous successive steps. Immuno-expression of BCL6 in all slides was assessed and noted in Annexure. Data were analyzed using SPSS version 21.Results: Patients included were 57. The mean age was 50.1 years. Males were 54%. The frequency of the BCL6 gene expression was 33%. The majority of the nodal cases were negative for BCL6 31%. Positive nodal cases were 16%. The majority of the extranodal cases were also negative for BCL6 36%. The positive extra nodal cases were 17%.Conclusion: BCL6 immunoexpression has a fair presence in DLBCL. It can be used as an adjunct tool in evaluating patients of DLBCL. Patients with positive BCL6 gene mutation can benefit from BCL6 specific target chemotherapy